Teatro de serviço e adoração: um estudo sobre o processo criativo do artista-servo da Igreja Batista da Agulha, no Grupo de Teatro Renascer - MOREIRA, Terezinha Cantanhede (2019)
This research shows a small historical demonstration of Christianity andconducts an overview of the presence of Art within the Baptist churches of the city of Belém, so as to establish comparisons between them and the university. However, its main focus is on the artistic production of Agulha Baptist Church,its theatre group, Renascer. This paperexposes the various scenarios carried out by the group, their creative principles and the artist-servants’ process. It is the same thing in the qualitative universe (SILVA; Menezes, 2005). The technique used is the case study (Gil, 2000), since these events have already occurred. Some other methodological procedures are also used, such as a collection of interviews with pastors and/or leaders of the Baptist churches of Belém, with current and former members of the group as well as with its founder; an analysis of these; a catalogue of dramaturgical texts; and photos taken from personal sources, from the group’s founder, from its former members and some members of the congregation in question. This research follows Fernando Peixoto (2007) to understand the concept of theater, Patrice Pavis (2007) to clarify concepts and classifications, and Richard Schechner (2004) as the author who plays a crucial role in understanding and analyzing the principles of this theatrical phenomenon.